Macroevolutionary Processes Driving the Asymmetric Latitudinal Diversity Pattern of Polyplacophorans Along the Eastern Pacific Coast - Cornejo, Claudio F.; Navarrete, Arturo H.; Reyes Gómez, Adriana; Sirenko, Boris; Maturana, Claudia S.; Hernández, Raquel; Rosenfeld Sekulovic, Sebastián Alejandro; Díaz, Angie; Ibáñez, Christian M.; Pardo Gandarillas, M. Cecilia (My University, 2025)
Aim: To assess the current latitudinal pattern of polyplacophoran diversity along the Eastern Pacific coast and determine how macroevolutionary processes are primarily responsible for their origin and distribution. Location: Eastern Pacific coast. Time Period: Present (2004–2023). Major Taxa Studied: Polyplacophorans. Methods: For each one-degree latitudinal band, we estimated species richness, species-by-genus ratio, species-by-family ratio, genus-by-family ratio, taxonomic distinctiveness, and standardised phylogenetic diversity. These metrics were derived from a database of 15,940 polyplacophoran records from the Eastern Pacific coast, comprising specimens collected in this study and specimens from biological collections. Phylogenetic relationships of 87 species inhabiting this region were reconsrtucted using mitochondrial (cox1) and ribosomal (16S, 18S, and 28S rRNA) genes. Results: The species richness of polyplacophorans in shallow waters displays an asymmetric unimodal pattern along the Eastern Pacific coast. In the Northern Hemisphere, values of species and genus richness, phylogenetic diversity, and ratios of species per genus and species per family, are consistently higher than those observed in the Southern Hemisphere. By contrast, the Souther Hemisphere shows lower-than-expected taxonomic distinctness and standardised phylogenetic diversity, with values remaining below those of the Northern Hemisphere. Interestingly, however, the higher latitudes of the Southern Hemisphere exhibit significantly greater taxonomic distinctness than expected. Overall, this asymmetric unimodal pattern is evident across six biogeographic regions, highlighting a clear hemispheric disparity in polyplacophoran diversity. Main Conclusions: The asymmetric unimodal pattern of polyplacophoran diversity in shallow waters off the Eastern Pacific coast provides clear evidence of macroevolutionary processes have been at work. This pattern indicates that speciation, extinction, and immigration have played a fundamental role in shaping species distributions in the Eastern Pacific coast. When integrated with previous research, these findings challenge the traditional biogeographic paradigm by suggesting that the notion of maximum diversity in the tropics does not universally apply to marine invertebrates. Instead, our results underscore the importance of considering both hemispheric asymmetries and evolutionary dynamics in explaining global biodiversity patterns.
Keywords: biogeography; chitons; latitudinal diversity; macroevolution; phylogenetic diversity; taxonomic diversity